Augustine of Hippo’s Critique of Philosophy in De civitate Dei - Domínguez Valdés, Patricio (Anales del Seminario de Historia de la Filosofía, 2017)
This article reconstructs panoramically the position of Agustine of Hippo towards philosophy in his work De civitate Dei. It holds that the judgement and criticism made by Augustine to the platonici rest ultimately on a concept of philosophy taken from Platonism itself and re-interpreted according to biblical texts which emphasize the centrality of mediation and cult to achieve the beata vita.